Exploring Managerial Dimensions in Dual Teaching Model for Communicative English Classroom: A Participatory Action Research in West Nusa Tenggara - Bayu Islam Assasaki; Emilia Agustina (Al-Qalam Institue, 2025)
The demand for effective English communication skills has surged globally, highlighting the need for innovative teaching models in language education. This study explores the impact of the Dual Teaching Model (DTM) within a Participatory Action Research (PAR) framework to enhance communicative English instruction at Institut Agama Islam Nurul Hakim Kediri, Indonesia. The study aimed to assess the model's effectiveness in improving students' fluency, accuracy, pronunciation, and interactional competence. Data were collected through pre and post-tests, classroom observations, focus group discussions, and teacher journals. The findings revealed significant improvements in all components of communicative competence, with the most notable gains in interactional competence (+16.1) and fluency (+14.9). Qualitative data supported these results, highlighting increased student engagement, confidence, and collaborative learning. The study concludes that the DTM fosters a more dynamic and interactive learning environment, promoting both linguistic and affective development. The research contributes to the field by demonstrating the effectiveness of co-teaching in enhancing communicative English instruction and providing insights into its scalability and adaptability for future digital integration.